2022
DOI: 10.1021/acs.organomet.2c00151
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Reactivity of an Iron Azametallacyclobutene Complex

Abstract: A variety of C–N bond-forming methods are enabled by the [2 + 2] cycloaddition reaction of a transition metal imide complex and an alkyne substrate to generate an azametallacyclobutene intermediate. This type of reactivity has been primarily limited to early transition metals like zirconium and titanium. Herein, we describe the preparation of an iron azametallacyclobutene complex by [2 + 2] cycloaddition of a β-diketiminate iron imide complex and an internal alkyne, 1-phenyl-1-propyne. The metallacycle reacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…24 Indeed, we demonstrated that the β-alkynyl enamine product of mesityl azide (MesN 3 where Mes = 2,4,6-trimethylphenyl) and phenylacetylene (Ar = phenyl) 1a undergoes cyclization in the presence of a copper(I) species to give the desired pyrrole 2a in 48% yield over two steps (Equation 1). 22…”
Section: Table 1 Optimization Of Cyclization Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Indeed, we demonstrated that the β-alkynyl enamine product of mesityl azide (MesN 3 where Mes = 2,4,6-trimethylphenyl) and phenylacetylene (Ar = phenyl) 1a undergoes cyclization in the presence of a copper(I) species to give the desired pyrrole 2a in 48% yield over two steps (Equation 1). 22…”
Section: Table 1 Optimization Of Cyclization Conditionsmentioning
confidence: 99%
“…Our previous work demonstrated that electron-donating and electron-neutral substituents are well tolerated in iron-catalyzed alkyne carboamination, while electron-withdrawing substituents are detrimental to the process. 22 However, copper-mediated cyclization appears to favor substrates that are more electron-poor. 25 These opposing electronic effects track with observations made during our evaluation of the arylacetylene scope using our optimized conditions for two-step/one-pot pyrrole synthesis (Scheme 2 ).…”
Section: Table 1 Optimization Of Cyclization Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 An azametallacyclobutene complex (X = NR) has the potential for electron delocalization throughout the ring system akin to a metallacyclobutadiene through involvement of electrons on nitrogen. We recently reported the isolation and characterization of the first monometallic iron azametallacyclobutene complex (1; Scheme 1b) 15 that was discovered during our investigation into the mechanism of iron-catalyzed alkyne carboamination. 16 Details from the molecular structure of 1 hinted at a delocalized π system within the metallacycle (vide infra).…”
Section: ■ Introductionmentioning
confidence: 99%